Exploring the Cloud Top Phase Partitioning in Different Cloud Types Using Active and Passive Satellite Sensors. Issue 2 (18th January 2021) - Bruno, Olimpia; Hoose, Corinna; Storelvmo, Trude; Coopman, Quentin; Stengel, Martin
Abstract: One of the largest uncertainties in numerical weather prediction and climate models is the representation of mixed‐phase clouds. With the aim of understanding how the supercooled liquid fraction (SLF) in clouds with temperature from −40°C to 0°C is related to temperature, geographical location, and cloud type, our analysis contains a comparison of four satellite‐based datasets (one derived from active and three from passive satellite sensors), and focuses on SLF distribution near‐globally, but also stratified by latitude and continental/maritime regions. Despite the warm bias in cloud top temperature of the passive sensor compared to the active sensor and the phase mismatch in collocated data, all datasets indicate, at the same height‐level, an increase of SLF with cloud optical thickness, and generally larger SLF in the Southern Hemisphere than in the Northern Hemisphere (up to about 20% difference), with the exception of continental low‐level clouds, for which the opposite is true. Plain Language Summary: In mixed‐phase clouds, hydrometeors consisting of ice and supercooled liquid water (i.e., water below 0°C) can exist simultaneously. In the mixed‐phase temperature range (−40°C to 0°C), ice‐nucleating particles (e.g., mineral dusts, biological aerosol particles) are needed for glaciation to be possible. The partitioning into liquid and ice depends not only on the ice‐nucleating particles, but also, for example, on cloud dynamics and ice multiplication processes, influencing in turn the lifetime and the precipitation type of these clouds, and the Earth‐atmosphere energy balance locally and globally. In this study, we show ice and liquid partitioning for different cloud types, comparing four satellite‐based datasets. This allows us to identify robustly their common trends despite their differences. Our results show on average less ice in the Northern than in the Southern Hemisphere when considering all clouds together, and that the larger the cloud optical thickness, the less ice when treating the cloud types separately. The partitioning of cloud types over sea and over land in both hemispheres show less ice in the Southern than in the Northern Hemisphere for high‐level and mid‐level clouds, but the opposite for low‐level clouds over land. This might be due to differences in aerosol composition and distribution. Key Points: Despite phase and temperature mismatches, the retrievals based on passive and active satellite sensors qualitatively agree on the following Supercooled liquid fraction is larger in the Southern Hemisphere than in the Northern Hemisphere, except for continental low‐level clouds In clouds with temperatures from −40°C to 0°C at the same height‐level, supercooled liquid fraction increases with cloud optical thickness